2019
DOI: 10.1111/jocn.14514
|View full text |Cite
|
Sign up to set email alerts
|

Exploring family members’ experiences during a death process in the emergency department: A grounded theory study

Abstract: Research findings reveal the need to create changes within clinical practice, regarding how to take care of the family involved in a death process in an emergency service. From the needs detected by the participants, it could be possible to implement an interventional program, which offers to the relatives the emotional support they may need. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Eight studies reported the family's “lack of information” experience related to bereavement (Bekkering & Woodgate, 2019; Berbís‐Morelló et al, 2019; Brysiewicz, 2008; Emond et al, 2019: S. P. Li et al, 2002; Merlevede et al, 2004; Parris et al, 2007; Punches et al, 2019). The patient's family experienced that the healthcare professionals did not tell, could not tell, or never really explained what was happening, and while waiting in the ED, experienced frustration, upset, pain, and a traumatizing time due to the lack of explanation offered (Emond et al, 2019; Punches et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight studies reported the family's “lack of information” experience related to bereavement (Bekkering & Woodgate, 2019; Berbís‐Morelló et al, 2019; Brysiewicz, 2008; Emond et al, 2019: S. P. Li et al, 2002; Merlevede et al, 2004; Parris et al, 2007; Punches et al, 2019). The patient's family experienced that the healthcare professionals did not tell, could not tell, or never really explained what was happening, and while waiting in the ED, experienced frustration, upset, pain, and a traumatizing time due to the lack of explanation offered (Emond et al, 2019; Punches et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies detailed the information that the family needed during the dying process, noting that the family wanted complete and up‐to‐date information so they could understand the care the patient was receiving to prepare themselves for possible outcomes, including death (Bekkering & Woodgate, 2019). They needed information about the patient's situation and health status, progression, and prognosis, as well as whether they had experienced any pain before dying (Berbís‐Morelló et al, 2019). The families also needed information after the death of the patient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Care for relatives is described as an integrated part of palliative care but often in a context where patient, relatives and healthcare professionals have established a relationship prior to death (The World Health Organization 2015, Sundhedsstyrelsen [Danish Health Authority] 2017). Palliative care for relatives and the BID persons are likely to obtain limited focus and low priority in the ED as the overarching goal in the ED is to save lives and maintain a high patient flow, consequently nurses and physicians are trained and acknowledged for their instrumental life-saving skills (Beckstrand et al 2012, Decker et al 2015, Hogan et al 2016, European Society For Emergency Medicine (EUSEM) 2017, Sundhedsstyrelsen [Danish Health Authority] 2017, Diaz-Cortes et al 2018, Berbis-Morello et al 2018). However, caring for BID persons and their relatives require different skills and competencies and must be rendered.…”
Section: Accepted Articlementioning
confidence: 99%